Plasthirst: The Potential of Water Dispenser Reverse Vending Machine in Plastic Bottle Waste Management - Jimenez, Mark Lester G.; Nazal, Cathlyn Joy M.; Canlas, Sebastian Lee H.; Sadie, Nel Eiram D.; Sombillo, Reyyin Angeline L.; Castor, Mary Joy M.; Amora, Althea B. (Journal of Sustainability and Environmental Management, 2025)
Plastics are commonly used for convenience, but improper disposal significantly harms marine ecosystems. Despite the presence of trash bins, plastic waste remains unmanaged, prompting researchers to develop Plasthirst, a machine that dispenses 200 ml of drinking water for every plastic bottle deposited, thereby promoting proper waste management. The study involved building a functional prototype using an ESP32 microcontroller, integrating components, and ensuring safety before pilot testing. A descriptive analysis evaluated Plasthirst’s response time and dispensing accuracy, as well as the factors influencing students’ utilisation of this machine. Meanwhile, correlational analysis revealed a very weak, non-significant relationship between bottle size and amount of water dispensed, r= - 0.06, p(0.81) > 0.05. However, a strong, significant positive correlation was shown between the number of bottles deposited and the amount of water dispensed, r = 0.99, p(0.00) < 0.05. All measured factors significantly influenced students’ engagement with Plasthirst. Based on the findings, the researchers recommend adding a 1–2-second delay to give users more time to deposit bottles and suggest upgrading to infrared or weight sensors to improve detection and adjust water dispensation based on bottle size. Testing the machine with at least five bottles is also advised for a more detailed analysis. Additionally, incorporating a QR code that links to educational material on recycling could further improve environmental awareness and user participation. Finally, following the proposed developmental plan is expected to enhance Plasthirst’s overall efficiency and impact.